2022
DOI: 10.1002/tie.22325
|View full text |Cite
|
Sign up to set email alerts
|

U.S.‐China trade war and competitive advantage of Vietnam

Abstract: China has been losing international competitiveness in labor‐intensive industries due to various factors, including the trade war with the United States and globalization. Vietnam, however, has rapidly expanded its labor‐intensive exports. The paper proposes to explore the future of labor‐intensive industries in Vietnam due to the U.S.‐China trade war. The paper examines export performance data from United Nation Comtrade for 10 specific labor‐intensive industries that serve the U.S. market between 2000 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This result slightly deviates from Guo and Luo [ 18 ], but also in conformity with Ha et al [ 19 ]. Moreover the result confirmed other related studies [ 26 ] stating that China has lost competitiveness in labor-intensive industries which includes the agricultural industry as this study result shows, while Vietnam’s competitive advantage in the agriculture trade is stronger than that of China’s.…”
Section: Results Analysis and Discussionsupporting
confidence: 89%
“…This result slightly deviates from Guo and Luo [ 18 ], but also in conformity with Ha et al [ 19 ]. Moreover the result confirmed other related studies [ 26 ] stating that China has lost competitiveness in labor-intensive industries which includes the agricultural industry as this study result shows, while Vietnam’s competitive advantage in the agriculture trade is stronger than that of China’s.…”
Section: Results Analysis and Discussionsupporting
confidence: 89%
“…In 2015, China introduced its Made in China 2025 strategy to upgrade technology comprehensively. Thus this reform led to dramatic increase in the organization affairs (Dhar et al, 2022). In order to ensure the smooth implementation of the change, the organization usually promulgates new organizational policies and systems and establishes new rigorous working procedures.…”
Section: Organizational Change and Work Pressurementioning
confidence: 99%
“…Dhar, Le, Coffelt, and Shaturaev (2023) [ 16 ] observed that factors such as the US-China trade war and globalization contributed to the ongoing decline in China's international competitiveness within labor-intensive industries. China's competitiveness saw a sustained downward trend through the latter part of 2020, while Vietnam's competitiveness exhibited a continuous rise.…”
Section: Introductionmentioning
confidence: 99%